Integrative analysis of the value & supply chains and its impact in supporting customer value An application study in Southern Cement Company - Kufa Cement Plant - جراد حيدر علي (Journal of Economics and Administrative Sciences, 2016)
Abstract The value chain analysis is main tools to achieve effective and efficient cost management; it requires a depth and comprehensive understanding for all internal and external activities associated with creating value. Supply chain as apart of value chain, that means managing it in active and efficient can achieve great results when adopting a comprehensive and integrated performance for these two chains activities. The research aims to identify possible ways to integrate the performance of value and supply chains of the sample" Kufa-cement plant" and determine the effect of this integration in enhancing customer value. The research arrival that logical and integrated analysis of value and supply chains helps to provide a clear vision to management which activities adding value along that chains.. The search recommendation are; continues work to development activities that contribute to adding value sustainability, and adopting teamwork to study and analyze these activities, as well as adopting an integrated internal and external relationships based on integration and sharing information, knowledge and benefits among all parts of value and supply chain, development transportation and handling processes among quarries and factory, and make a benchmarking with successful.references.